KORELASI KADAR ASAM URAT DALAM DARAH TERHADAP LUARAN KLINIS STROKE ISKEMIK AKUT - Daniel Mahendrakrisna,* Aria Chandra Gunawan Triwibowo Soedomo** (NEURONA, 2020)
BACKGROUND URIC ACID IS AN END METABOLISM PRODUCT OF PURINE IT HAS BEEN KNOWN AS AN IMPORTANT ANTIOXIDANT IN THE SERUM CORRELATION BETWEEN URIC ACID SERUM WITH STROKE HAS BEEN REPORTED CONTROVERSIAL FINDING HOWEVER URIC ACID HAS BEEN PROPOSED TO BE A STROKE RISK FACTOR